2013
DOI: 10.1371/journal.pone.0064739
|View full text |Cite
|
Sign up to set email alerts
|

Golden Berry-Derived 4β-hydroxywithanolide E for Selectively Killing Oral Cancer Cells by Generating ROS, DNA Damage, and Apoptotic Pathways

Abstract: BackgroundMost chemotherapeutic drugs for killing cancer cells are highly cytotoxic in normal cells, which limits their clinical applications. Therefore, a continuing challenge is identifying a drug that is hypersensitive to cancer cells but has minimal deleterious effects on healthy cells. The aims of this study were to evaluate the potential of 4β-hydroxywithanolide (4βHWE) for selectively killing cancer cells and to elucidate its related mechanisms.Methodology and Principal FindingsChanges in survival, oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
111
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 42 publications
3
111
0
1
Order By: Relevance
“…[28] Additionally, increased ROS production could result in increased DNA damage. [29] Previous studies have also shown that DNA damage stimulates ROS production through the H2A.X-Nox1/Rac1 signaling pathway. [30] In our study, we found that blue LED irradiation increased ROS production and induced DNA damage in BMSCs.…”
Section: Discussionmentioning
confidence: 98%
“…[28] Additionally, increased ROS production could result in increased DNA damage. [29] Previous studies have also shown that DNA damage stimulates ROS production through the H2A.X-Nox1/Rac1 signaling pathway. [30] In our study, we found that blue LED irradiation increased ROS production and induced DNA damage in BMSCs.…”
Section: Discussionmentioning
confidence: 98%
“…A wide range of cellular stress, such as stress at mitochondria [33], Golgi apparatus [34], endoplasmic reticulum [35] and nucleus [36], has been suggested to interrupt cell cycle progression, leading to G1 arrest. Reevesioside A induced G1 arrest of the cell cycle followed by apoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence demonstrated that ROS generation and mitochondrial membrane depolarization may lead to DNA damage [33,34,35,36,37,38] and apoptosis [38,39,40,41] in drug-treated cancer cells. Accordingly, TFB also showed a correlation between oxidative stress and DNA damage in its antiproliferative and apoptotic effects of two oral cancer cells (Ca9-22 and CAL 27) in our study.…”
Section: Discussionmentioning
confidence: 99%
“…DNA double strand breaks were detected by both flow cytometry [48] and Western blotting [35] as described previously. For flow cytometry, TFB-treated cells were fixed, washed, and incubated at 4 °C for 1 h in 2 μg/mL of p-Histone H2AX (Ser 139) (γH2AX) monoclonal antibody (sc-101696; Santa Cruz Biotechnology, Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%